Influence of embedment, self-weight and anisotropy on bearing capacity reliability using the random finite element method. (June 2015) - Pieczyńska-Kozłowska, J.M.; Puła, W.; Griffiths, D.V.; Fenton, G.A.
Abstract: The paper expands on previous work by the authors on bearing capacity of random c ′ - ϕ ′ soils using the random finite element method. The refinements in the present work include the influence of embedment, soil self-weight and anisotropy which were not considered previously. The study focuses on a grey-blue clay from Taranto in Italy, for which stochastic strength parameters were well documented. Results show that the influences of embedment, self-weight and anisotropy can be significant and lead to more realistic estimates of bearing capacity reliability. Finally a probability distribution of the bearing capacity was estimated and used to calibrate safety factors for reliability purposes.